THE EFFECT OF PRECURSORS CONCENTRATION ON THE STRUCTURE AND MICROMAGNETIC PROPERTIES OF ULTRAFINE IRON OXIDES OBTAINED BY SOL-GEL ROUTE - V. O. Kotsyubynsky; V. V. Moklyak; A. B. Hrubiak; L. V. Mohnatska; M. I. Gasyuk (Vasyl Stefanyk Precarpathian National University, 2016)
Nanodispersed composite materials g-Fe2O3/a-Fe2O3 were obtained by thermal decomposition of iron citrate xerogel hydrate synthesized by iron nitrate and citrate acid solutions with different colloidal solutions of Fe(NO3)3×9H2O and С6Н8О7 ×Н2О for different molar ratio between precursors. The influence of the precursors molar concentration and calcination temperature on the material phase composition, crystalline and magnetic microstructure, surface condition was studied. Methods of X-ray diffraction, Mössbauer spectroscopy, electron microscopy and IR - spectroscopy were used.